Health‐related quality of life questionnaires in individuals with haemophilia: a systematic review of their measurement properties. Issue 4 (21st April 2017) - Limperg, P.F.; Terwee, C.B.; Young, N.L.; Price, V.E.; Gouw, S.C.; Peters, M.; Grootenhuis, M.A.; Blanchette, V.; Haverman, L.
Abstract : Background: The evaluation of health related quality of life (HRQOL) is essential for a full assessment of the influence of an illness on patients' lives. The aim of this paper is to critically appraise and compare the measurement properties of HRQOL questionnaires studied in haemophilia. Methods: Bibliographic databases (Embase, Medline, Cinahl and PsycInfo) were searched for articles evaluating measurement properties of HRQOL questionnaires in haemophilia. Articles were excluded that did not report HRQOL measurement properties, or when <50% of the study population had haemophilia. The methodological quality of the selected studies was evaluated using the COSMIN checklist. The measurement properties of the HRQL questionnaires were rated as 'positive', 'indeterminate' or 'negative', accompanied by levels of evidence. Results: The search resulted in 1597 unique hits, of which 22 studies were included. These articles evaluated three questionnaires for children (CHO‐KLAT, Haemo‐QoL and one unnamed measure) and five for adults (Hemofilia‐QoL, Haemophilia Well‐Being Index, HAEMO‐QoL‐A, Haem‐A‐QoL, and SF‐36). The CHO‐KLAT was the paediatric measure that showed the strongest measurement properties in high‐quality studies. The Haemophilia Well‐Being Index and HAEMO‐QoL‐A performed best among the adult measures. None of the studies reported measurement error and responsiveness. Conclusion: Our findings suggest that there is no need for new disease‐specific HRQOL questionnaires for haemophilia, but rather that additional research is necessary to document the measurement properties of the currently available questionnaires, specifically focusing on the structural validity, measurement error and responsiveness of these questionnaires.